2014
DOI: 10.3109/21678421.2014.906618
|View full text |Cite
|
Sign up to set email alerts
|

Increased iron level in motor cortex of amyotrophic lateral sclerosis patients: An in vivo MR study

Abstract: Amyotrophic lateral sclerosis (ALS) is one of the most common neurodegenerative disorders, but no definite mechanism has been defined on the loss of motor neurons in ALS and currently no therapy can block its progression. Many lines of evidence indicate that there is a disorder of iron homeostasis in ALS, and thus we sought to test the iron level in ALS patients by susceptibility weighted imaging (SWI). Sixteen ALS patients and 16 healthy persons underwent brain scans using SWI with a 3T Siemens MR scanner. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…By contrast, the Caucasian patients assessed previously lived in developed countries (26), and likely had greater access to treatments and adequate nutrition compared with patients in the present study, which may explain the significant increase in serum ferritin reported (26). Our previous study indicated that iron levels are increased in the motor cortex of patients with ALS by using susceptibility weighted imaging (48). The majority of the patients with ALS in the present study also participated in our aforementioned previous study.…”
Section: Discussionmentioning
confidence: 52%
“…By contrast, the Caucasian patients assessed previously lived in developed countries (26), and likely had greater access to treatments and adequate nutrition compared with patients in the present study, which may explain the significant increase in serum ferritin reported (26). Our previous study indicated that iron levels are increased in the motor cortex of patients with ALS by using susceptibility weighted imaging (48). The majority of the patients with ALS in the present study also participated in our aforementioned previous study.…”
Section: Discussionmentioning
confidence: 52%
“…Later studies found a correlation being T2* shortening and iron deposition in the microglia of the motor cortex (according to a post-mortem examination) [7, 106, 108]. Iron overload in the motor cortex was also described in SWI studies [109] and qualitative studies [100]; in the later study, there were no differences between ALS patients and controls in terms of T2 or T2*. A few quantitative studies have looked at white matter or deep grey matter [109, 110].…”
Section: Resultsmentioning
confidence: 99%
“…Langkammer et al (6) identified increased iron deposition in localized regions along the corticospinal tract in ALS patients (6). Corroborating these findings, it was previously reported that phase shift values were significantly higher in the motor cortex of patients with ALS using susceptibility weighted imaging, indicating increased iron levels in this area (7). Additionally, pathological studies have demonstrated increased iron accumulation in the motor cortex of patients with ALS (8).…”
Section: Introductionmentioning
confidence: 84%